The role of life events in obsessive-compulsive disorders - Mandal, Uday Sankar; Mallick, Suchismita; Surjendu Bikash Khatua; Mondal, Arijit; Sandip Kumar Hazra (Asian Journal of Medical Sciences, 2024)
Background: A small number of studies are available to assess the role of stressful life events (SLEs) in obsessive-compulsive disorder (OCD). The previous studies have reported contradictory results and they have methodological limitations. Aims and Objectives: The objectives of our study are (i) to find out the frequency of life events in patients with OCD in comparison to their matched healthy controls and (ii) to find out the impact of life events on the severity of the disorder. Materials and Methods: Sixty patients fulfilling Diagnostic and Statistical Manual of Mental Disorder, 5th edition (DSM-V) criteria of OCD were rated with Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Hamilton Rating Scale for Anxiety (HAM-A), Hamilton Rating Scale for Depression (HAM-D), and Presumptive Stressful Life Events Scale (PSLES). A group of 60 normal controls were also rated on PSLES. Finally, both groups were compared in terms of life events. Results: The frequency of life events, past 1 year (t=5.307, P=0.006) and lifetime (t=11.527, P<0.001), were significantly higher in the patient group in comparison to controls. PSLES scores showed a significant correlation with Y-BOCS total scores, Y-BOCS obsession scores, and HAM-A scores. There was a positive correlation between past 1 year PSLES score and HAM-D scores. Step-wise linear regression analysis showed PSLES scores significantly positively predicted Y-BOCS total score, Y-BOCS obsession score, and Y-BOCS compulsion score. Conclusion: Life events were significantly more frequent in OCD patients both past 1 year and lifetime, as compared to healthy controls. The severity of obsessive compulsive symptoms was found to be directly proportional to the number of SLEs experienced in the past 1 year and lifetime.